Advances in self-powered sports monitoring sensors based on triboelectric nanogenerators - Sun, F.; Zhu, Y.; Jia, C.; Zhao, T.; Chu, L.; Mao, Y. (Journal of Energy Chemistry, 2023)
The new era of the internet of things brings great opportunities to the field of intelligent sports. The collection and analysis of sports data are becoming more intelligent driven by the widely-distributed sensing network system. Triboelectric nanogenerators (TENGs) can collect and convert energy as self-powered sensors, overcoming the limitations of external power supply, frequent power replacement and high-cost maintenance. Herein, we introduce the working modes and principles of TENGs, and then summarize the recent advances in self-powered sports monitoring sensors driven by TENGs in sports equipment facilities, wearable equipment and competitive sports specialities. We discuss the existing issues, i.e., device stability, material sustainability, device design rationality, textile TENG cleanability, sports sensors safety, kinds and manufacturing of sports sensors, and data collection comprehensiveness, and finally, propose the countermeasures. This work has practical significance to the current TENG applications in sports monitoring, and TENG-based sensing technology will have a broad prospect in the field of intelligent sports in the future.